Business Process Reengineering (BPR): rejuvenate the business licensing process in a local government / Muhammad Ridhwan Ab. Aziz … [et al.] - Ab. Aziz, Muhammad Ridhwan; Abdul Shukor, Syadiyah; Ahmad Bustamam, Ummi Salwa; Mohamed, Zainal Abidin (Faculty of Administrative Science and Policy Studies, 2012)
Government’s transformation plans are being implemented in various ministries and departments at the Federal level and are supposed to trickle down to the state and district levels as well. We have heard of several on-line systems, “PEMUDAH” and “BLESS” where issues on bureaucracy (amongst others) are being looked into. Developing entrepreneurship and small business have also being given a fair focus to help the respective sectors play their role in the country’s 2020 vision. This paper looks at the other end of the spectrum by looking into some of the issues faced by the small business enterprises with respect to the bureaucracy that they had to endure when trying to sustain their ways of living. Although one case study is presented, it depicts the fundamental or ground level issues being experienced that can be generalized and looked from a bigger perspective. Encik Lukas (not his real name) waited for 3 months to get his business license approved and thus removed his status as an “illegal business man” (which was much longer). ‘But, why 3 months, he lambasted?’ This paper then probed and discusses what goes on in the respective Majlis Perbandaran Tempatan (MPT), and followed his application documents and discovered the kinds of bureaucracy (required process flow) that it had to go through. The paper then suggests the kinds of actions and changes that can be considered resulting in the process time being reduced by 80%. This will be a transformation and thus a business process reengineering recommendation!